Navigating the Depths of Cancer Stem Cells: Unraveling Resistance Mechanisms and Emerging Therapeutic Strategies - Gajanan Sapate; Rutuja Shinde; Swaraj Tawale; Dipak Pawar (Recent Trends in Infectious Diseases, 2023)
In the past few decades, comprehensive evidence has convincingly established the presence of cancer stem cells (CSCs) as a minor subset within tumors, contributing to an unusually elevated level of cellular diversity within the malignancy. CSCs are functionally identified by their capacity for self-renewal and differentiation, frequently influenced by signals from their surrounding microenvironment. The interconnected transcriptional, post-transcriptional, metabolic, and epigenetic regulatory networks govern the biological characteristics of CSCs. CSCs contribute to tumor growth, therapeutic resistance, and disease recurrence by prolonged proliferation, invasion into normal tissue, angiogenesis enhancement, immune system evasion, and resistance to traditional anticancer therapy. As a result, understanding the molecular pathways behind cancer stem cell persistence, adaptability, and therapeutic resistance would increase our capacity to improve treatment.
Keywords: Cancer; Cancer stem cells; Future perspectives; Tumor microenvironment; therapy resistance